Illegal Turtle Trade in Bac Kan, Quang Ninh, Tuyen Quang Provinces and Online Illegal Turtle Trade - Tran, Thi Khanh Linh (ĐHQGHN, 2017)
Turtle trade is a long-term conservation problem, which drives many turtle populations in Vietnam to the brink of extinction. In this study, we conducted interview surveys in three northern provinces in Vietnam, including Bac Kan, Quang Ninh, and Tuyen Quang between 2013 and 2015 to investigate the scale and trend of turtle trade in Vietnam. The results of the study show that the prices of most species increased alarmingly during the study period, probably due to the rarity of the species and the higher demand from China. More importantly, our surveys of online trading activities through social networks suggest that the new method of turtle trade dramatically rises in recently years, and overtakes the traditional networks as the most common way of trading. Based on the trend and scale of the trade, we recommend several conservation measures to mitigate turtle trade, especially formulating new regulations to stop online trading activities.